Prototype Pengadaan Dan Distribusi Barang Pada Waralaba Fried Chicken dan Burger lampung - Dona Yuliawati; Sushanty Saleh; Indera Indera (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2018)
Based on the research data, it is that the leader of Master Fried Chicken and Burger have difficulties about stock and good distribution activities as delayof stock and goods distribution, hoarding goods in warehouse, file duplication, hard file finding, information given are not accurate and takes long time in searching the data as it has no reports provided to leaders even in stock reports or in goods distribution report. The method used in this research is orientasi design analysis with the use of UML model using Netbeans IDE 6.0. tools and to make Master Fried Chicken and Burger needs stock and goods distributions system which are developed to be a program using java programming language. The system made can report which are not existed before like goods data report. Kiosk data, staff data and supplier data. Bisedes, this system can print road letter, purchasing application letter, report of stock and goods distribution perkioask per period faster by inputting number or period of printed date. By using this stock and goods distribution, it is expected to help Master Fried Chiken and Burger in controlling its stock and goods distribution.Keywords: Procurement; Distribution of goods; UML